Blowing-out effect in flame retarding epoxy resins: Insight by temperature measurements during forced combustion. (September 2016) - Zhang, Wenchao; Fina, Alberto; Cuttica, Fabio; Camino, Giovanni; Yang, Rongjie
Abstract: The temperature measurements within burning epoxy resins (EPs) were used to study the thermo physical evolution up and inside of samples during different applied heat fluxes cone calorimeter tests. A series of flame retarded epoxy resins (EP) were prepared with polyhedral oligomeric silsesquioxane containing 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-POSS). The flame retardancy of these EPs was tested by both flammability tests (LOI, UL-94) and forced combustion in cone calorimeter, to assess DOPO-POSS effects on the flame retardancy of EP composites. 2.5 wt% DOPO-POSS incorporation into epoxy resin perform interesting blowing-out effect, which results in a LOI value 27.1 and UL-94 V-1 ( t 1  = 8 s and t 2  = 5 s) rating. The details of fire behavior, such as the values of TTI, HRR, p-HRR, and THR have been tested using a cone calorimeter. The temperature measurements during cone calorimeter tests indicate that the char layer of EP/2.5 DOPO-POSS has the best performance on heat insulation and play an effective role (heat insulation) quicker than that of EP/5 DOPO-POSS or EP/10 DOPO-POSS. This heat insulation performance of char layer produced by EP/2.5 DOPO-POSS explains its good performance on LOI and UL-94 test.